2015
DOI: 10.4236/ajps.2015.65072
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Antibacterial and Antioxidant Activities of Essential Oils of <i>Mentha viridis</i> L. and <i>Mentha pulegium</i> L. (L)

Abstract: The essential oils from Mentha viridis L. and Mentha pulegium L. were characterized by gas chromatography coupled to mass spectrometry (GC-MS). These oils were obtained by hydrodistillation and presented linalool (40.70%), carvone (13.52%) and α-terpinene (8.56%) as the principal constituents in the essential oil from Mentha viridis L. Pulegone (50.01%), menthol (31.90%) and menthone (16.56%) were the principal constituents in the essential oil from Mentha pulegium L. These essential oils (in concentrations ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
(20 reference statements)
1
16
0
Order By: Relevance
“…Silva et al [36] evaluated the antioxidant activity of the essential oil from the plants of the Lamiaceae family (Mentha pulegium and Mentha viridis) by the molybdenum reduction method. They found that a higher activity was observed for the essential oil from M. pulegium (50.0% of pulegone, 31.9% menthol and 16.6% menthone) than for the standard used (BHT), followed by the essential oil from M. viridis, which is composed of 40.7% linalool, 13.9% carvone and 8.6% α-terpinene.…”
Section: Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al [36] evaluated the antioxidant activity of the essential oil from the plants of the Lamiaceae family (Mentha pulegium and Mentha viridis) by the molybdenum reduction method. They found that a higher activity was observed for the essential oil from M. pulegium (50.0% of pulegone, 31.9% menthol and 16.6% menthone) than for the standard used (BHT), followed by the essential oil from M. viridis, which is composed of 40.7% linalool, 13.9% carvone and 8.6% α-terpinene.…”
Section: Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%
“…Silva et al [36] observed a limited activity in reducing the iron ion for the essential oil from M. viridis. However, the activity observed for the essential oil from M. pulegium at the concentrations of 0.78 to 50 µL•mL −1 exceeded that of the BHT standard.…”
Section: Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%
“…The antibacterial activity was determined using the Agar Cavity Diffusion technique according to the method described by Silva et al [9]. …”
Section: Antibacterial Activity Of the Essential Oilmentioning
confidence: 99%
“…Only very few reports on the determination of the antioxidant activity of the essential oil using Phosphomolybdenum assay and applied for of T. vulgaris were found in literature [7][8][9]. For these reports, the antioxidant values are difficult to use for comparison purpose since different methods of expressions or different antioxidant of reference were engaged.…”
Section: Introductionmentioning
confidence: 99%